Impact on Selected Aspects of the Supply Chain Logistics in the light of the 2025 US Tariff Policy: Case Study. /The experience of COVID-19/ - Łukasz WACŁAWIK (Communications of International Proceedings, 2025)
Companies operate in an increasingly difficult to predict environment. Their environment is subject to continuous change due to innovations as well as to black swan events. A black swan event is a high-impact event that is difficult to predict. Global black swans that have emerged recently include the COVID-19 pandemic, Russia’s aggression against Ukraine and President Trump’s tariff policy. The only typical black swan here is the COVID pandemic. The other two events result from the unpredictability of human actions. COVID-19 caused several changes in the functioning of companies. There are already many research works showing how supply chains changed as a result of the pandemic. However, there is a lack of analyses that would show how the COVID-19 experience helps in the attempts to adapt to the tariffs proposed by the US government. Therefore, it is worth considering whether the COVID experience will make it easier to adapt to the unpredictability of the US tariff policy. The object of the research is a large Polish manufacturing company, a significant exporter with manufacturing plants also outside the European Union. The research is an attempt to assess adaptation processes in the supply chain caused by the new US customs policy in the light of the COVID-19 experience. The article is based on an interview with a long-time purchasing manager, who developed the company’s purchasing policy during the pandemic, and it tries to determine how the company’s operations will change as a result of the new US customs policy. Today, it is difficult to draw conclusions from the example in question as the article includes only the first observations. It seems that, among other things, due to the changes caused by the pandemic, the company is prepared for the new US tariff policy. The biggest threat, however, is that the US market is the market with the highest added value and its potential loss could have profound consequences.
Keywords: supply chain; production; Black Swan; COVID